1990
DOI: 10.1128/aac.34.6.963
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity for humans of human rhinovirus type 2 mutants resistant to or dependent on chalcone Ro 09-0410

Abstract: Mutants of human rhinovirus type 2 (HRV-2) resistant to and dependent on the antirhinoviral compound chalcone Ro 09-0410 were selected in cell culture under clean laboratory conditions. A total of 42 volunteers were challenged with either the drug-resistant mutant ,ug of amphotericin B (Fungizone) per ml, 1 mg of neomycin per ml, 50 IU of penicillin G per ml, and 100 ,ug of streptomycin per ml.The methods used for growing and determining the infectivity of human rhinovirus type 2 (HRV-2) in tissue culture wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…In that study, several poliovirus mutants displayed intermediate levels of resistance (2-to 4-fold increases in inhibitory concentrations), while one variant was highly resistant (over a 10-fold increase) to neutralization. The levels of sICAM-1 resistance of HRV-39 variants that we have reported are comparable to the resistance levels previously observed for single-step to sevenfold increases in EC50s) (10) (20). One study reported the recovery of HRV-9 resistant to a capsid-binding agent, R618367, after a human experimental infection (6), in which 32% of the treated volunteers shed resistant viruses at some point.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In that study, several poliovirus mutants displayed intermediate levels of resistance (2-to 4-fold increases in inhibitory concentrations), while one variant was highly resistant (over a 10-fold increase) to neutralization. The levels of sICAM-1 resistance of HRV-39 variants that we have reported are comparable to the resistance levels previously observed for single-step to sevenfold increases in EC50s) (10) (20). One study reported the recovery of HRV-9 resistant to a capsid-binding agent, R618367, after a human experimental infection (6), in which 32% of the treated volunteers shed resistant viruses at some point.…”
Section: Discussionsupporting
confidence: 71%
“…Of note, poliovirus variants selected for resistance to soluble poliovirus cell receptors, despite their reduced binding to HeLa cells, did not differ significantly from the wild-type virus with regard to the kinetics of viral replication in vitro or neurovirulence for mice (12). Although there are conflicting data on the ability of HRVs selected for resistance to a capsid-binding agent, chalcone Ro 09-0410, to grow in cell cultures (1,21), one resistant HRV-2 variant was found to have significantly reduced infectivity for humans (20). Further characterization of the sICAM-1-resistant phenotype, including its ability to replicate in human cell lines and respiratory cell epithelium, is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…In a study conducted with laboratory-isolated drug-resistant mutants of RVs, infectivity of the virus was reduced significantly (Yasin et al, 1990). This result is consistent with laboratory observations with drug-resistant coxsackievirus B3, which showed a marked reduction in virulence in mice compared with wild-type virus .…”
Section: Drug Resistancesupporting
confidence: 77%
“…We conclude by discussing a specific case study: the treatment of picornaviruses with pleconaril (Yasin et al 1990;Pevear et al 1999;Hayden et al 2003). Picornaviruses, which include enteroviruses and rhinoviruses, are the most ubiquitous pathogens of humans.…”
Section: Discussionmentioning
confidence: 99%